The Influence of Culture on Consumer Impulsive Buying Behavior - Kacen, Jacqueline J.; Lee, Julie Anne (Journal of Consumer Psychology, 2002)
Impulse buying generates over $4 billion in annual sales volume in the United States. With the growth of e‐commerce and television shopping channels, consumers have easy access to impulse purchasing opportunities, but little is known about this sudden, compelling, hedonically complex purchasing behavior in non‐Western cultures. Yet cultural factors moderate many aspects of consumer's impulsive buying behavior, including self‐identity, normative influences, the suppression of emotion, and the postponement of instant gratification. From a multi‐country survey of consumers in Australia, United States, Hong Kong, Singapore, and Malaysia, our analyses show that both regional level factors (individualism–collectivism) and individual cultural difference factors (independent –interdependent self‐concept) systematically influence impulsive purchasing behavior.